1966
DOI: 10.1021/bi00874a016
|View full text |Cite
|
Sign up to set email alerts
|

On the Existence of Spectrally Distinct Classes of Flavoprotein Semiquinones. A New Method for the Quantitative Production of Flavoprotein Semiquinones*

Abstract: This work was performed during tenure of Career Development Award GM-K3-31.213.1 Abbreviations used: epr, electron paramagnetic resonance;FMN, riboflavin 5'-phosphate; TPNH, reduced triphosphopyridine nucleotide; FAD, FADH, FADHi, oxidized, semiquinoid, and fully reduced flavin-adenine dinucleotide; TPN+, oxidized triphosphopyridine nucleotide.cals, which are very readily distinguished on the basis of their optical absorption properties. With one enzyme, glucose oxidase, both types of radical are found, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
280
3

Year Published

1967
1967
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(316 citation statements)
references
References 23 publications
33
280
3
Order By: Relevance
“…The about ten-fold increase in stability constant when going from water to the less polar solvent dimethylformamide indicates that metal flavin radical chelates could have a considerable stability when the flavin is situated in a partly hydrophobic crevice of a protein. The anionic character of the radical ligand is interesting since anionic radicals have been observed in flavoenzymes [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…The about ten-fold increase in stability constant when going from water to the less polar solvent dimethylformamide indicates that metal flavin radical chelates could have a considerable stability when the flavin is situated in a partly hydrophobic crevice of a protein. The anionic character of the radical ligand is interesting since anionic radicals have been observed in flavoenzymes [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…The blue radical species 5-Hill can be further stabilized chemically by alkylation, as shown with the derivatives 5-R61 [49] or biochemically via binding to a suitable apoprotein, as found in the wide-spread group of 'blue radical flavoproteins' [7,9] . In all cases where flavin radicals could be shown to act as catalytically essential intermediates, the radicals are of the blue variety 5-H61, and the stabilization is thought to be brought about by a regiospecific hydrogen bridge pointing from the apoprotein towards N(5) (see below).…”
Section: Reactivity Of the Radical Statesmentioning
confidence: 99%
“…By stabilization through hydrogen bonding to these same centers, it is possible that a similar situation may exist in flavoprotein red radicals. Hence, as mainly disregarded in the earlier literature, red flavoprotein radicals can either be anions Fl-or neutral tautomers of the type l-or 2a-Rl?l, and a clear distinction is only possible in those few cases where a radical pK is seen in the protein-bound state, such as glucose oxidase [7] and lysine monooxygenase [55] . Furthermore, whenever a flavoprotein exhibits a red radical, it appears that the radical state is biocatalytically nonessential, i.e., the red radical cannot be generated by the action of substrates, but only artificially.…”
Section: Reactivity Of the Radical Statesmentioning
confidence: 99%
“…Also a large excess of benzoate considerably lengthens the time for photoreduction of L-amino acid oxidase a t pH 8. 3 and glucose oxidase at pH 6.…”
Section: Photoreduction Of Flavins and Flavoproteinsmentioning
confidence: 99%
“…Recently Massey and Palmer [3] demonstrated that several flavoproteins could be photoreduced with EDTA, but other potential photoreductants were not examined.…”
mentioning
confidence: 99%